Analisis Prinsip Kerja Sama dalam Acara Komedi Extravaganza - Faizal Arvianto (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Ilmu Pendidikan, Universitas Timor, 2019)
In language studies, there is a study of the use of language which is intended as an effort to guide conversation participants to be able to carry out cooperative conversations, namely pragmatic studies, especially in the part of the principle of cooperation. Grice divides four maxims which establish the principle of cooperation. The four maxims are the maxims of Quality, quantity, relationships, and ways. The object of the study in this analysis is the comedy Extravaganza program